Discovery of a 0.8-mHz quasi-periodic oscillation in the transient X-ray pulsar SXP31.0 and associated timing transitions - Salganik, Alexander; Tsygankov, Sergey S.; Molkov, Sergey V.; Lapshov, Igor Yu.; Lutovinov, Alexander A.; Tkachenko, Alexey Yu.; Mushtukov, Alexander A.; Poutanen, Juri (EDP Sciences, 2026)
We present the first broadband spectral and timing study of the Be/X-ray pulsar XTE J0111.2−7317 (SXP31.0) during the first major outburst since its discovery in 1998. This giant type II outburst, observed between April and September 2025, marks the source’s return to activity after nearly three decades of quiescence. Using NuSTAR observations together with data from Swift/XRT and SRG/ART-XC, we followed the outburst’s evolution, with the source reaching a bolometric luminosity of Lbol = 3.6 × 1038 erg s−1. The broadband spectra are well described by an absorbed cutoff power law, two blackbody components (hot and soft), and a narrow Fe Kα line. No cyclotron absorption features were detected in either the phase-averaged or phase-resolved spectra in the 5–50 keV band. Most notably, we report the discovery of a previously undetected quasiperiodic oscillation (QPO) at 0.8 ± 0.1 mHz, characterized by a fractional root-mean-square (rms) amplitude of 14% at a super-Eddington bolometric luminosity of Lbol = 2.5 × 1038 erg s−1. In contrast, the previously reported 1.27 Hz QPO was not detected. While the 0.8 mHz QPO is present, the pulsed fraction (PF) is low in soft X-rays, which is consistent with other super-Eddington pulsars exhibiting mHz QPOs; however, it rises above 20 keV to reach 35%. The QPO vanishes in subsequent observations coinciding with a sharp increase in the PF and a distinct change in pulse profile morphology. It was not observed in any follow-up observations at luminosities above or below its initial detection, suggesting it is a transient phenomenon.